Discordance between distance ambulated as part of usual care and functional exercise capacity in survivors of critical illness upon intensive care discharge: Observational study - Waters, A.; Hill, Kylie; Jenkins, S.; Johnston, C.; Mackney, J. (American Physical Therapy Association, 2015)
© 2015 American Physical Therapy Association. Background. People who have had a prolonged admission to an intensive care unit (ICU) commonly have profound debilitation and weakness. For the delivery of effective exercise training, an accurate assessment of exercise capacity is essential. Objective. The study objectives were to investigate how much ground-based walking is undertaken by inpatients recovering from critical illness within 1 week of discharge from an ICU and to evaluate the feasibility and safety of the Six-Minute Walk Test (6MWT) for this population. Design. This was an observational study. Methods. Within 1 week of discharge from the ICU, functional exercise capacity was measured with the 6MWT. The maximum distance ambulated on the ward in a single session as part of usual clinical management was extracted from the medical notes. The distance achieved during the 6MWT and the maximum distance ambulated on the ward were compared. Results. The participants (N=23) were survivors of a critical illness; their mean age was 57 years (SD = 11). The median length of ICU stay was 11 days (interquartile range [IQR]=7). The mean 6-minute walk distance (6MWD) was 179 m (SD = 101), and the maximum distance ambulated on the ward was 30 m (IQR=65). There was a moderate association between the distance participants ambulated on the ward and the 6MWD (r=.54). The maximum distance ambulated on the ward, expressed as a percentage of the 6MWD, was 29% (IQR=34%). Five participants (22%) experienced oxygen desaturation (oxygen saturation of <85%) and recovered within 1 minute of resting. Limitations. The maximum distance ambulated on the ward was estimated with premeasured distances. Conclusions. Most participants ambulated at a low percentage of their measured exercise capacity. The 6MWT appears to be a safe and useful test for inpatients recently discharged from the ICU.